Loyalist Instruction of Kairsu: Section 14 (O. NMEC 339) - Marwa Ewais (Shedet, 2021)
This paper publishes the hieratic ostracon (O. NMEC 339) stored in the National Museum of Egyptian Civilization at Cairo, discovered during Edda Bresciani's excavations at Gurna in Thutmose IV temple in the 1970s. Its exact provenance in the temple is unknown, but it is among a group of hieratic ostraca that was found. The ostracon is a literary fragment inscribed with section 14 of a Loyalist Instruction of Kairsu, considered one of the important literary texts from the Middle Kingdom and New Kingdom. This ostracon is a novel addition to the 18th Dynasty corpus of this composition, which is better known from its Ramesside version.